Unraveling Sustainability Transitions, Path Creation, and Opportunity Space for Sustainable Development Policy: A Conceptual Literature Review - Avendaño-Leadem, Daniel (2024)
This conceptual literature review explores the nuanced terrain of sustainability transitions, path creation, and opportunity space within the theoretical framework of evolutionary economic geography. Grounded in the foundational principles of this field, which examines the spatial and temporal dynamics of economic evolution, the paper applies a systematic approach to meticulously select and analyze twelve scholarly articles dated from 2010 or after. The methodology involved the creation of a comprehensive database organizing and systematizing the relevant data, so offering a robust foundation for the exploration of theoretical approaches and constructs related to sustainability transitions, path creation, and opportunity space. Drawing from the field of evolutionary economic geography, the paper emphasizes key contributions from this theoretical perspective. A common thread identified across these concepts is the pivotal role of change agency. The paper concludes by underlining the contributions of sustainability transitions, path creation, and opportunity space to sustainable development policy, providing insights into their potential impact on shaping a more sustainable and resilient future.